Management of human talent and the job satisfaction of workers from a private educational institution - Bendezú-Pacífico, karen I. (2020)
The objective of the research work was to determine the relationship between the management of human talent and the job satisfaction of the workers of the Private Educational Institution "Mave School", San Juan de Lurigancho, Lima, 2019. The methodology used was descriptive correlational. For data collection, two instruments were developed for both variables taken from the SL / SPC Labor Satisfaction Scale - by Sonia Palma, with a sample of 18 teachers and 06 administrators. The results indicated that the management of human talent is significantly related to the job satisfaction of the workers of the Private Educational Institution "Mave School", San Juan de Lurigancho, Lima; then it was concluded that the correlation was significant and reached a level of 0.892 that corresponds to a strong correlation level.